COMPARASION OF THE ANALYTICAL THINKING ABILITY IN THE SIMPLE MACHINE MATERIAL BETWEEN GUIDED INQUIRY LEARNING MODEL AND STUDENT TEAM ACHIEVEMENT STUDENT DIVISION (STAD) OF PRIMARY SCHOOL STUDENTS - Annis Maulia Fatimahtuzzahroh; Peduk Rintayati; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2018)
The study was aims to determine the differences between the analytical thinking ability of student that taught by Guided Inquiry learning model within the analytical thinking ability of student that taught by STAD learning model. The study used pre experimental type of quantitative approach with One Group Pretest-Posttest Research Group Design. The samples were taken by purposive sampling with a 5th grade students at Soropadan primary school as experimental 1 and a 5th grade students Karangasem III primary school as experimental 2. The data were collecting technique by doing test. The instrument was tested using factor analysis. The data were analyzed using descriptive analysis and statistical parametric consisted of prerequisite test (normality and homogeneity test), hypothesis test (T-test) and N-gain score. Based on the results of t-test analysis at significance level α = 0.05, showed that tobtained (2.604) > ttable (1.99). It can be concluded that there is difference between the analytical thinking ability of student that taught by Guided Inquiry learning model and taught by STAD